THE INFLUENCE OF BLENDED LEARNING ON READING COMPREHENSION IN SECONDARY SCHOOL ENGLISH CLASSES - Otajonova Ziyoda Abzaljon qizi; Azimbayeva Dilafruz Abdujabarovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: Blended learning, which integrates both online and in-person instructional methods, has emerged as a significant strategy in contemporary education. Within secondary school English classes, enhancing reading cognition stands as an important goal that impact students’ academic achievements. This research investigates the effects of blended learning on the enhancement of reading comprehension skills in English as a Foreign Language (EFL) students. Results demonstrate that the fusion of digital tools with traditional classroom teaching boosts student engagement and yields better comprehension results. The research underscores the educational significance of technology-enhanced language instruction.